STUDI PEMBUATAN NUGGET BERBAHAN DASAR TAHU DENGAN TAMBAHAN SAYURAN - Khatimah, Nurul; Kadirman, Kadirman; Fadilah, Ratnawaty (Universitas Negeri Makassar, 2018)
This study aims to determine the effect of using basic ingredients of tofu with additional vegetables for nugget quality, as well as the level of fondness for nuggets. The type of this research is quantitative research with experiment approach using randomized block design consisting of control 100% of chicken meat, 90% tofu and 10% broccoli, tofu 85% and broccoli 15%, tofu 80% and broccoli 20%. The results showed that the highest water content was 90% tofu and 10% broccoli, while the highest protein content was 85% tofu and 15% broccoli. The results of organoleptic test showed that the best treatment on color, aroma, taste, and texture indicator was tofu 85% and broccoli 15%